EKSTRAKSI MULTI TAHAP KURKUMIN DARI KUNYIT (Curcuma domestica Valet) MENGGUNAKAN PELARUT ETANOL - Rajian Sobri Rezki, Dwimas Anggoro, Siswarni MZ (Jurnal Teknik Kimia USU, 2015)
Curcumin is a pigment in Curcuma domestica Valet, which has an orange-yellow crystal appearance, and commonly being used as a colouring agent. Extraction method which is used in extracting curcumin from Curcuma domestica Valet is one stage extraction. This research studied a multi stages extraction of curcumin from Curcuma domestica Valet. The purposes of this research is to find the best condition in extracting curcumin using multi stages extraction method, to increase the efficiency rate in curcumin extraction. This research used ethanol as a solvent, and effect from variables such as extraction time, solvent concentration, and number of extraction stages are observed. Extraction times are 60 minutes, 120 minutes, and 180 minutes. Variations of ethanol concentration are 50%, 70%, and 96%. Stage numbers of extraction are two stages extraction and three stages extraction. Extracts of curcumin are examined with qualitative analysis and quantitative analysis. The best condition of multi stages curcumin extraction is determined based on yield and content of curcumin. The maximum yield obtained in this study was 12% with conditions 180 minutes extraction time, 96% ethanol concentration, and two stages extraction. The highest content of curcumin obtained is 16% with conditions 180 minutes extraction time, 96% ethanol concentration, and three stages extraction. Content means a fraction of yield. These results show that increase in extraction time, solvent concentration, and stage numbers of extraction  will increase the yield and content of curcumin extracted from Curcuma domestica Valet.